A new Species of Neonemura (Plecoptera: Notonemouridae), and Records of Stoneflies from Aisén Province, Region XI, Chile - Stark, Bill P. (Illiesia, 2013)
Neonemura copa sp. nov. is described from a male specimen collected from a tributary to Lago Copa in Aisén Province (Region XI), Chile, and records for nine additional stonefly species are presented for the province.
Keywords: entomology; Notonemouridae; Plecoptera; Neonemura; distribution; Lago Copa; Chile; Cisnes Municipality